2019
DOI: 10.1002/2211-5463.12727
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of kiss2 and gpr54‐2 in Monopterus albus suggest these genes may play a role in sex reversal in fish

Abstract: Due to its exceptionally small genome size and protogynous hermaphroditism, Monopterus albus has been proposed as a model for vertebrate sexual development. The Kiss/GPR54 system is a central regulator of sexual development in most vertebrates, but its role in sex reversal remains hypothetical. In contrast to mammals, fishes often possess more than one copy of the kiss and gpr54 genes. Our objectives were to identify all kiss/gpr54 genes in the genome of M. albus and to assess their involvement in sex reversal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed multiple sex-related genes that might be involved in sex change, gonadal differentiation in M. albus , and other teleosts ( Zhang et al, 2008 ; Wu et al, 2012 ; Hu et al, 2014 ; Hu et al, 2015 ; Gao et al, 2016 ; Cai et al, 2017 ; Yi et al, 2019 ; Ding et al, 2020 ; Chen et al, 2022 ; Feng et al, 2022 ). To investigate a genomic survey of these genes in the assembled genome, these genes were directly searched in the annotated genome using gene name or identified with tBlastn (v2.9.0+) ( Camacho et al, 2009 ) in the annotated genome.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed multiple sex-related genes that might be involved in sex change, gonadal differentiation in M. albus , and other teleosts ( Zhang et al, 2008 ; Wu et al, 2012 ; Hu et al, 2014 ; Hu et al, 2015 ; Gao et al, 2016 ; Cai et al, 2017 ; Yi et al, 2019 ; Ding et al, 2020 ; Chen et al, 2022 ; Feng et al, 2022 ). To investigate a genomic survey of these genes in the assembled genome, these genes were directly searched in the annotated genome using gene name or identified with tBlastn (v2.9.0+) ( Camacho et al, 2009 ) in the annotated genome.…”
Section: Methodsmentioning
confidence: 99%